2013
DOI: 10.1111/joa.12094
|View full text |Cite
|
Sign up to set email alerts
|

What is the origin of the arterial vascularization of the corpora cavernosa? A computer‐assisted anatomic dissection study

Abstract: The purpose of this study was to identify the microscopic arterial vascularization of the corpora cavernosa (CC) of the penis using computer-assisted anatomic dissection (CAAD), determine the contribution of the different penile arteries towards this vascularization, detail the nature of cavernospongiosum shunts, and locate the anastomoses between these different arteries. Tissue specimens were taken from five donors who donated their bodies to science. The specimens were fixed in 10% formalin and sliced into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…This has been confirmed by functional magnetic resonance imaging studies of the regional activation of the male genital sensory cortex, which illustrated a sensory innervation of the deep penile tissue [22]. The cavernourethral vascular anastomoses are also innervated by the autonomic system, joining with the urethral and bulbourethral arteries [9].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This has been confirmed by functional magnetic resonance imaging studies of the regional activation of the male genital sensory cortex, which illustrated a sensory innervation of the deep penile tissue [22]. The cavernourethral vascular anastomoses are also innervated by the autonomic system, joining with the urethral and bulbourethral arteries [9].…”
Section: Discussionmentioning
confidence: 70%
“…It was also observed that, in the mobile part of the penis, both DNPs and CNs accompanied vascular anastomoses between the dorsal and the cavernous arteries of the penis. As a group, they establish the neurovascular intrapenile axis, which includes the dorsosomatic pathways (originating from underneath the levator ani muscle) and the cavernoautonomic pathways (originating from above the levator ani muscle) [9,19]. The number of these dorsocavernous arterial anastomoses is known to be variable; between two and four were identified in each individual in the present study [20].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The fibrous bands firmly attached to the urethral wall with a constant thickness, or undulated while interrupted by the arteries of carvenospongiosum shunts (Diallo et al. ) and spongiosum tissues. This architecture did not reach the distal tip of the glans penis when it had a blunt end or radial shape (35.5% of cases).…”
Section: Resultsmentioning
confidence: 99%
“…Effective pharmacological treatment of ED requires the delivery of vasoactive agents to the corpora cavernosa and retention within this compartment. Several studies, using microdissection [28,29] or spongiographic radiological contrast techniques [30,31] have described the presence of both arterial and venous shunts, that could constitute a viable route for delivery of vasoactive drugs from the surface of the spongiosal glans penis to the cavernosal compartment. As shown schematically in Fig.…”
Section: Delivery Of Vasoactive Agents To the Corpus Cavernosummentioning
confidence: 99%